Examining Responsible Furniture Design in Terms of Sustainability: A Review on Cafe Furniture - Tunca, Oğuzhan (Eastern Mediterranean University, 2021)
ABSTRACT: The concept of sustainability is generally referred to as being permanent. Today, with the effect of population growth and increasing resource consumption, the concept of sustainability has gained great importance. Sustainable design is responsible for society and the environment, so designers should understand the importance of sustainability in designs and develop creative solutions. Especially in the public spaces that the society uses in common, the designs that people interact with the most are furniture. Independent organizations in sustainable furniture design prepare various standards and certification systems. However, in these certification systems, environmental sustainability criteria are prioritized, and the score weight is higher. To develop furniture in a human-centered manner, a need was felt for an evaluation system in which social sustainability has an equal value with environmental sustainability. The aim of this study is to create a checklist that can help architects and interior architects in the problem of sustainable furniture design, evaluating environmental and social sustainability equally. In addition, since the existing sustainable furniture certification systems have a complex scoring system, designers are hesitant to approach sustainability. This research aims to help designers to design sustainable furniture by preparing this checklist that can be easily followed during the design process. For this purpose, as the first step a vast literature review was realized to define environmental and social sustainability and to find out the current criteria for sustainable furniture design which shaped the base for the proposed checklist. Then, using the suggested checklist, chairs and table furniture in selected cafes in Çanakkale are evaluated in terms of environmental and social sustainability. In the case study, the researcher experienced the field practice in situ and collected data with measurements, photographs, and drawings. By using the information and experiences obtained, the checklist for sustainable furniture design and the evaluation tables of the furniture were created and the study was concluded by summarizing the findings. Keywords: Furniture Design, Environmental Responsibility, Social Responsibility, Public Space, Sustainability, Eco-Friendly Use

ÖZ: Sürdürülebilirlik kavramı genel olarak kalıcı olma şeklinde tanımlanmaktadır. Günümüzde nüfus artışı ve artan kaynak tüketiminin etkisiyle sürdürülebilirlik kavramı büyük önem kazanmıştır. Sürdürülebilir tasarım toplumdan ve çevreden sorumludur, bu nedenle tasarımcılar tasarımlarında sürdürülebilirliğin önemini anlamalı ve yaratıcı çözümler geliştirmelidir. Özellikle toplumun ortak kullandığı kamusal alanlarda insanların en çok etkileşime geçtiği tasarımlar mobilyalardır. Sürdürülebilir mobilya tasarımında bağımsız kuruluşlar tarafından çeşitli standartlar ve sertifikasyon sistemleri hazırlamaktadır. Ancak bu sertifikasyon sistemlerinde çevresel sürdürülebilirlik kriterleri ön planda tutulmakta ve puan ağırlığı daha yüksek olmaktadır. Mobilyaları insan merkezli geliştirmek için sosyal sürdürülebilirliğin çevresel sürdürülebilirlik ile eşit değerde olduğu bir değerlendirme sistemine ihtiyaç duyulmuştur. Bu çalışmanın amacı, sürdürülebilir mobilya tasarımı probleminde mimarlara ve iç mimarlara yardımcı olabilecek, çevresel ve sosyal sürdürülebilirliği eşit olarak değerlendiren bir kontrol listesi oluşturmaktır. Ayrıca mevcut sürdürülebilir mobilya sertifikasyon sistemleri karmaşık bir puanlama sistemine sahip olduğundan, tasarımcılar sürdürülebilirliğe yaklaşmaktan çekinmektedirler. Bu araştırma, tasarım sürecinde kolaylıkla takip edilebilecek bu kontrol listesini hazırlayarak tasarımcıların sürdürülebilir mobilya tasarlamalarına yardımcı olmayı amaçlamaktadır. Bu amaçla, ilk adım olarak, çevresel ve sosyal sürdürülebilirliği tanımlamak ve önerilen kontrol listesinin temelini şekillendiren sürdürülebilir mobilya tasarımı için mevcut kriterleri bulmak amacıyla geniş bir literatür taraması gerçekleştirilmiştir. Ardından, önerilen kontrol listesi kullanılarak Çanakkale şehrinde seçilen kafelerdeki sandalye ve masa mobilyaları çevresel ve sosyal sürdürülebilirlik açısından değerlendirilmektedir. Vaka çalışmasında araştırmacı, saha uygulamasını yerinde deneyimlemiş ve ölçümler, fotoğraflar ve çizimlerle verileri toplamıştır. Elde edilen bilgilerden ve deneyimlerden yararlanılarak sürdürülebilir mobilya tasarımı için oluşturulan kontrol listesi ile mobilyaların değerlendirme tabloları oluşturulup bulgular ile özetlenerek çalışma sonlandırılmıştır. Anahtar kelimeler: Mobilya Tasarımı, Çevresel Sorumluluk, Sosyal Sorumluluk, Kamusal Mekan, Sürdürülebilirlik, Çevre Dostu Kullanım
Master of Science in Interior Architecture. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Architecture, Dept. of Interior Architecture, 2021. Supervisor: Asst. Prof. Dr. Guita Farivarsadri
Keywords: Thesis Tez; Interior Architecture; Interior Design - Cafes - Sustainable Furniture Design; Interior Design - Architecture and Design - Sustainability; Interior architecture - Cafes and Restaurants; Furniture Design; Environmental Responsibility; Social Responsibility; Public Space; Sustainability; Eco-Friendly Use